IMPROVING THE NUTRITIONAL VALUE OF WATER HYACINTH LEAVES (WHL) AND ADDING IT TO BROILER DIETS AND ITS EFFECT ON THE PRODUCTIVE PERFORMANCE. - Ali M. Al-Aboudi; S. J. Hamodi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted at the poultry farm , Animal Production Department , Shatrah Technical Institute / Southern Technical University for the period from 13/11/2020 to 25/12/2020 (42 days), to find out the effect of improving the nutritional value for water hyacinth leaves (WHL) fermented with Saccharomyces cerevisiae yeast (Sc) and fermented with Iraqi probiotic at different levels and its effect on the productive performance of broilers chickens. In the experiment, 300 day old unsexed Ross 308 broiler chicks were. The chicks were fed on a starter ration for 1-21 days of age and a finisher ration form 22-42 days of age. The birds were randomly distributed in to 10 treatments, with 3 replicates for each treatment (10 birds for replicates),the treatments were as follows: T1 Control without any replacement, T2 replacement (WHL) powder at a level 6% instead of wheat, T3 Replacement (WHL) powder treated With (Sc) yeast at a level 6% instead of wheat, T4 replacement (WHL) powder treated with probiotics at a level of 6% instead of wheat, T5 replacement (WHL) powder at a level 12% instead of wheat, T6 replacement (WHL) powder treated with (Sc) yeast at a level 12% instead of wheat, T7 replacement (WHL) powder treated with probiotics at a level 12% instead of wheat, T8 replacement (WHL) powder at a level 18% instead of wheat, T9 replacement (WHL) powder treated with (Sc) yeast at a level 18% instead of wheat and T10, replacement (WHL) powder treated with probiotics at a level 18% instead of wheat, The results showed an improvement in live body weight, weight gain, feed consumption and food conversion ratio for all addition treatments compared with control. Treatments T2,T6 and T7 recorded the best results in productive characteristics.